Znaczenie słowa geniusz w wyrażeniu geniusz kobiety/kobiecy w czterech tekstach Jana Pawła II - Makuchowska, Marzena Jadwiga (Verbum Vitae, 2022)
The article analyses the meaning of the word genius in the expression feminine genius, which was introduced into the Catholic Church’s discourse on gender by Pope John Paul II. The author shows that this new use of the word genius is based on its already existing meanings, but is not identical with them. The new sense is understood broadly as a set of judgments of different status, having both a subjective character (connected with someone’s concept) and a discourse character (included in the "order" of a given discourse, in this case the Catholic discourse). In the descriptive layer, genius (feminine/feminine) signifies the (essentialist and complementary) essence of gender, but also very important is the highly positive meaning of the word, which connotes (and at the same time communicates) information about being exceptional, extraordinary, distinguished by the fact of belonging to one’s gender, and it is a message addressed mainly to women.